The Meaning of Social Criticism in the Song Fragile (玻璃心/ Bōlíxīn) Namewee ft. Kimberley Chen: Critical Discourse Analysis of Van Dijk - Muslimat, Andi Filsah; Halidun, Wa Ode Siti Hardianti (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2025)
This research aims to determine the discourse structure (text), social cognition, and social context in the song Fragile" (玻璃心/Bōlíxín) text, the results of this research show that the song Fragile (玻璃心/Bōlíxín) by Namewee in collaboration with Kimberley Chen. This research method uses qualitative research methods with Van Dijk's critical discourse analysis. The technique in this research is using data collection techniques, data analysis, and presenting results to draw conclusions. Based on text analysis, the results of this research indicate that the song Fragile (玻璃心/Bōlíxín) Expression and Music as a Medium of Resistance. The superstructure which contains the text schematic shows the existence of a text framework starting from the intro as the opening melody, the verse as the opening lyrics, the pre-chorus the pre-chorus is the transition section that connects the verse with the chorus, the refrain which is the core and climax of the song, the bridge which has different variations of all song structures which functions as a bridge or diverts the atmosphere of the song in terms of tone, lyrics and emotion, the final chorus which is followed by an outro to close the song . Micro structure as a local meaning shows criticism and protests against the government regarding the government's sensitivity when receiving criticism and limitations in expressing and expressing opinions. Apart from criticizing the government, this song also highlights the defensive attitude of Little Pinks, who are known as pro-government youth who have an extreme nationalist attitude but are wrapped in romantic lyrics and a cute, funny and creative video clip. Meanwhile, the social cognition of this song utilizes international collective knowledge regarding the sensitivity of the Chinese government and netizens to criticism, as well as the social context that plays a role in how this song is consumed by society. The social context of this song also shows different reactions from Chinese society and from outside China.